Factors Influencing Surgical Outcome of Patients with Traumatic Acute Subdural Hematoma - Narayan Dhar; Md Rabiul Karim; Mohammad Humayun Rashid; Mohammad Sanaullah; Mahfujul Quader; Md Motasimul Hasan; Tapas Sarker; Md Shahnewaz; Abul Hasan Md Touhidur Reza; Md Kamal Hossain; Majed Sultan; Asiful Islam (Bangladesh Journal of Neurosurgery, 2024)
Background: Traumatic acute subdural hematoma (ASDH) is a catastrophic devastating component of brain injury in neurosurgical arena. Due to its significant mortality rate, potential for functional disability and disastrous consequence of complications, it is considered as a challenge for neurosurgeons worldwide. Consequently, precise recognition of predictive outcome factors is crucial for appropriate neurosurgical management and prognostication for patients with traumatic ASDH. Aims: The study aimed to determine the demographic, clinical, radiological and therapeutic factors associated with the surgical outcomes in patients with traumatic acute subdural hematoma (ASDH) who managed surgically in the Neurosurgery Department at a tertiary level hospital in Bangladesh. Materials and Methods: This prospective observational study included 40 radiologically diagnosed cases of traumatic ASDH age more than 18 years who were admitted and operated in the Department of Neurosurgery of Chittagong Medical College Hospital from May 2022 to April 2023. Data regarding demographic, clinical, radiographic, surgical procedure and findings were recorded. Three months mortality rate with clinical outcome was assessed by Glasgow Outcome Scale (GOS) score and analyzed. The outcome was divided into favorable outcomes (GOS score >3) and unfavorable outcomes (GOS score d”3). Results: The median age of the patients was 45 years (range: 19-82 years), and there was a male predominance (82.5%) with a male to female ratio of 4.7:1. Road traffic accident (RTA) was the most common cause of trauma (65%), followed by fall from height (15%), and physical assault (12.5%). Craniotomy was done in 16 (40%) patients and other 24 (60%) patients had decompressive craniectomy. Overall, 21 (52.5%) patients had good outcome and other 19 (47.5%) had poor outcome, and three months mortality rate was 42.5%. Regression analysis revealed that, increasing age [Odds ratio (OR): 1.12, 95% Confidence interval CI: 1.02-1.22. p=0.014], preoperative GCS of d”8 (OR: 13.98, 95% CI:1.22-160.00, p=0.034), and presence of Anisocoria with non-reacting pupil (OR; 17.99, 95% CI: 1.32-244.08, p=0.030) were independently associated with poor outcome. Conclusions: This study identified higher age, preoperative low GCS score and pupillary abnormality as the independent predictors for 3-months poor outcome in patients who underwent surgical treatment for traumatic ASDH Bang. J Neurosurgery 2024; 13(2): 140-148